Influence of Ultrasonic Cavitation on Botryococcus Braunii Growth - SALAEH, Asleena (Archives of Acoustics, 2024)
This study investigates ultrasonic energy’s impact on enhancing the growth of Botryococcus braunii (B. braunii) microalgae. Microalgae, known for their advantages in greenhouse gas mitigation and biomass conversion, were subjected to various stressors, including ultrasonic waves, to optimize productivity. Ultrasonic waves induce acoustic cavitation, increasing membrane permeability and substrate conversion. The study examined the impact of energy and maximum pressure resulting from bubble collapse on the relative specific growth rate of B. braunii microalgae. It was observed that reproduction showed a promotive trend until the energy surpassed 30 kJ. However, when ultrasonic energy reached 18.2 kJ, reproduction was inhibited due to the maximum pressure generated during bubble bursting, which reached 5.7 μN/μm^2, leading to the suppression of reproduction upon encountering bubble collapse events. Under specific ultrasonic conditions (15.1 kJ energy, maximum pressure of 45.5 × 10^5 Pa), a maximum specific growth rate of 0.329 ± 0.020 day^−1 in a two-day interval boosted B. braunii microalgae biomass productivity. These findings advance our understanding of ultrasonic wave effects on microalgae reproduction and underscore the potential for optimizing ultrasonic parameters to enhance biomass production.